Contribuições do arranjo para a construção de sentido na canção brasileira: análise de três canções de Milton Nascimento. - Kristoff Silva (2011)
The present research focuses the theory developed by Luiz Tatit - named Semiótica da Canção, whose model for analising song writing has been widely adopted in the academic environment. Our goal was to investigate through which tools the musical thought has its influence in the configuration and enlargement of song interpretation, observing the misunderstandings of significance that the arrangement may cause in a composition, by pointing out specific aspects regarding the dialogue between lyrics and melody. Therefore, the main purpose was the application of the same concepts of the Semiótica da Canção to the analysis of the elements found in the structure of the arrangement.Three songs by Milton Nascimento were chosen: Cais, Um gosto de sol and Que bom, amigo, the two first ones written in colaboration with Ronaldo Bastos. These songs present in their form the repetition of various melodic-harmonic passages, performed each time in a different instrumental setting and also with contrasting interpretation.